Carbon Footprint Assessment of Two Photovoltaic Plants - Ribeiro, David Barbosa; Nogueira, Teresa Alexandra Ferreira Mourão Pinto (Neutro à Terra, 2024)
As the world moves towards sustainable energy sources to reduce the impacts of climate change, photovoltaic (PV) systems have become a crucial player in the renewable energy sector. This study evaluates the carbon footprint linked with the life cycle of PV plants. The aim is to give valuable insights into the environmental effects of their deployment. This article analyzes and compares the greenhouse gas emissions of two solar photovoltaic plants in Portugal. Both plants have the same equipment, peak power, and nominal power for injection into the grid. The only difference between them is the metal structure that supports the photovoltaic modules: plant A has a 2V tracker-type structure, and plant B has a 2V fixed structure. By comparing the two, it will be possible to determine the effect of the different structures on greenhouse gas emissions and the total energy output over the plant's 30-year lifespan.